Synovial Myxoma: Found in Canines, Rabbits, and Now Humans Too?. Issue 1 (January 2020) - Munger, Alana M.; Ibe, Izuchukwu K.; Rottmann, Douglas; Conway, Devin; Costa, José; Lindskog, Dieter M.
Abstract : Case: A 63 year-old woman presented with a multiple-year history of right knee pain and effusions and pain refractory to numerous knee aspirations and an arthroscopic synovectomy. The patient underwent a 2-incision synovectomy and intralesional resection. A pathologic review of the specimens revealed an infiltrative tumor of basophilic, cluster of differentiation 68-positive synovial cells embedded within a myxoid stroma with low proliferative activity, most consistent with a synovial myxoma. Conclusions: This case report of a synovial myxoma—a benign, slow growing but locally aggressive mass that is most commonly found in canines—indicates that the lesion may occasionally occur in humans.